The Existence of Jurisdiction to Realize Legal Currency in the United States of the Republic of Indonesia - Johamran Pransisto; Rachman Rizal Andi Sapada; Suardi Suardi; Nurnadhilah Bachri; Arini Asriyani (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This article examines the existence of jurisdiction in realizing legal currency within the context of the Republic of Indonesia. Judicial power, as an independent branch of government, plays a crucial role in upholding the rule of law and ensuring justice based on Pancasila. The judiciary must adjudicate cases without discrimination, utilizing various legal sources, including unwritten laws, to ensure fair outcomes. The study highlights the importance of integrating customary law into judicial decision-making, reflecting Indonesia's pluralistic society. However, challenges arise in identifying and applying these norms within the national legal framework. The article also addresses the implications of enforcing written laws and customary norms, particularly regarding sanctions for violations. Furthermore, it emphasizes the urgency of research in this area to evaluate and adjust the judicial system for equitable justice, strengthen judicial independence, and improve the effectiveness of special and religious courts. By analyzing these aspects, this study aims to contribute to a comprehensive understanding of Indonesia's legal landscape and its alignment with societal values